The clinical significance of peripheral blood cell ratios in patients with intracranial aneurysm - Kim, Hyun Kyung; Lee, Kee Ook; Oh, Seung-Hun; Lee, Kyung-Yul; Choo, Seung-Wook; Kim, Ok Joon; Kim, Tae Gon; Kim, Sang-Heum; Na, Sang-Jun; Heo, Ji Hoe (Frontiers in Neurology, 2022)
Background & Objective: Inflammation is an important factor in the development of aneurysm, and has been identified as a key characteristic predictive of rupture of intracranial aneurysm (IA). However, the role of inflammatory peripheral blood cell ratios in patients with IA has not been well delineated. Methods: A total of 1209 patients, including 1001 with unruptured IA and 208 with ruptured IA, were enrolled in this study. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platelet-to-neutrophil ratio (PNR), and platelet-to-white-blood-cell ratio (PWR) were compared between ruptured and unruptured IA. Results: Compared with the ruptured IA group, the unruptured IA group had higher PNR median, 65.96 [interquartile range (IQR) 48.95–85.05] vs. 37.78 (IQR, 23.17–54.05); p < 0.001 and PWR [median, 36.89 (IQR 29.38–44.56) vs. 22.39 (IQR, 16.72–29.29); p < 0.001]. In multivariate analysis, PNR and PWR were independently associated with ruptured IA (p = 0.001 and p < 0.001, respectively). Unruptured IA subgroup analyses according to the PHASES scores showed that a higher PHASES score was associated with significantly higher NLR and erythrocyte sedimentation rate (p < 0.001 and p = 0.025) and lower PNR and PWR (p < 0.001 and p = 0.007). Conclusions: We demonstrated that lower PNR and PWR levels are associated with ruptured IA and a higher PHASES score. Unlike many other inflammatory markers and bioassays, peripheral blood cell ratios are inexpensive and readily available biomarkers that may be useful for risk stratification in patients with cerebral aneurysm. However, a long-term prospective study is needed to clarify this matter.